The underlying cause of the simple virilizing phenotype in patients with 21-hydroxylase deficiency harboring P31L variant - Zhao, Zhiyuan; Gao, Yinjie; Lu, Lin; Tong, Anli; Chen, Shi; Zhang, Wei; Zhang, Xiaoxia; Sun, Bang; Wu, Xueyan; Mao, Jiangfeng; Wang, Xi; Nie, Min (Frontiers in Endocrinology, 2023)
Objective: To analyze the relationship between genotype and phenotype in 21-Hydroxylase deficiency patients harboring P31L variant and the underlying mechanism. Methods: A total of 29 Chinese patients with 21-OHD harboring P31L variant was recruited, and the detailed clinical features of the patients were extracted and analyzed retrospectively. The TA clone combined with sequencing of the region containing the promotor and exon1 of CYP21A2 was performed to determine whether the variants in promotor and P31L aligned in cis. We further compared the clinical characteristics of 21-OHD patients between the promoter mutation group and no promoter mutation group. Results： Among the 29 patients diagnosed with 21-OHD harboring P31L mutation, the incidence of classical simple virilizing form was 62.1%. Thirteen patients owned promoter mutations (1 homozygote and 12 heterozygote) and all exhibited SV form. The promoter mutations and the P31L mutation were located in the same mutant allele as validated by TA cloning and sequencing. There were statistically significant differences in clinical phenotype and 17-OHP level between the patients with and without promoter region variations (P<0.05). Conclusion: There exists high incidence (57.4%) of SV form among the 21-OHD patients harboring P31L mutation, and the underlying mechanism is partially due to both the promoter mutations and P31L aligning in cis on one allele. Further sequencing of promoter region will provide important hints for the explanation of phenotype in patients harboring P31L. Keywords：21-Hydroxylase deficiency, classical simple virilizing, promoter mutation, P31L